(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
Fable is a type of didactic story in which the characters are generally personified animals and whose narrative events usually illustrate, in a way that is intended to be persuasive, a certain maxim or moral principle. Such a maxim or principle is usually made explicit at the end of the story through verses or sententious phrases that constitute a moral. For this reason, this type of story has a relatively simple structure: the characters lack, at least in appearance, psychological depth; Descriptions of space and environment are limited to only the notations that are just and necessary to place the action in a minimum space-time framework. Fables, to the extent that they explain their morals, are proposed as “closed stories” in the sense that the narrator (or character) himself provides a precise reading key. That is, the story tends to restrict as much as possible the plural meaning of the literary text, inciting a defined interpretation, aimed at producing an ethical-moral intervention in the reader.